Pengaruh Edukasi melalui Media Booklet terhadap Pengetahuan Ibu Nifas dalam Pemberian ASI pada Bayi Usia 0–3 Hari - Githa Koeserawati Darise; Nelfa Fitria Takahepis; Helly.M.Katuuk (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Breast Milk is a food source that contains complete nutrition for babies. One of the factors that influences failure in providing breast milk is lack of knowledge. The purpose of this study was to determine the effect of education through booklet media on the knowledge of postpartum mothers in providing breast milk to babies aged 0-3 days at Manembo-Nembo Hospital Type C Bitung. The method used in this study was a pre-experiment with a one group pre and post design research design. The sample taken was 35 respondents using Total Sampling. Data collection used SAP and questionnaire sheets. The collected data were processed using the IBM SPSS Version 23 computer. For the analysis test using Wilcoxon with a significance level (α <0.05). The Wilcoxon statistical test obtained a value of ≤ ρ = (α<0.000). This means that Ha is accepted or there is a significant influence between the influence of education through booklet media on the knowledge of postpartum mothers in providing breast milk to infants aged 0-3 days